Labor Values and Attitudes of Modern Students - V. V. Retivina (Moscow Polytechnic University, 2019)
Labor values, professional attitudes, preferences and orientations largely determine the young people's labor behavior. The article presents an analysis of modern students' values in the field of labor and their place in the structure of basic values. The research was performed with the use of sociological data on the basis of a representative sample of 627 students ofNizhny Novgoroduniversities. The ambitions and requirements of the younger generation for future work and an assessment of the importance of the basic values are considered in detail. Five groups of individual labor mindsets are identified as a result of the factor analysis procedure application. Students' attitude to their future profession and the level of students' awareness of the labor conditions in this field have been considered. The research also revealed the influence of various agents on the young people' professional choice, gender differences in this issue.